Evaluation of condyle- fossa position and articular eminence angulation in dentate and edentate patients - A cephalometric pilot study - Pradhuman Verma; Princy Mahajan; Samar Ali Faraz; Konkati Srikanth; B Ravichandra; Natasha Bathla (Wolters Kluwer Medknow Publications, 2020)
Background: Temporomandibular joint is a mobile synovial joint where articulated bones are separated by a joint cavity. Its functional harmony is disrupted by a long standing period of edentulousness which could be analyzed using lateral Cephalograph. Aim and Objectives: To evaluate the condyle-fossa position and articular eminence angulation in dentate and edentate patients using a lateral cephalogram along a different axis. Materials and Methods: Cross-sectional study consisted of randomly selected 40 patients with 20 dentulous patients (Group I), and age- matched 20 completely edentulous patients (Group II), within an age group 45-65 years. Lateral cephalograms were performed for all selected patients using single Kodak 8000C digital OPG/Ceph machine, (Rochester, New York, United States). All the radiographs were digitally traced and evaluated twice for condyle- fossa position along X and Y axis and articular eminence angulation by an Oral & maxillofacial radiologist at an interval of two days. The collected data was tabulated and analyzed using SPSS Software version 20 using unpaired t-test and tests of normality. Results: Significant difference in condyle - fossa distances along the X and Y axis in two study groups was suggestive of more upwards and forwardly placed condyles and more anteriorly placed glenoid fossae in Group II patients. Also, articular eminence angulation was noted more in edentulous patients but the difference was statistically insignificant. Conclusion: A great variation in condylar-fossa position was observed in the edentulous patient when compared to the dentulous patient due to remodeling or degenerative changes that occur during the period of edentulousness.